Semantic aspects of somatic polysemy in the quechua Ayacucho- chanca : the cases of uma 'head' and simi 'mouth' - Gálvez Astorayme, Isabel (2017)
Lexemes related to human anatomy in Quechua Ayacucho-Chanca transgress the literal (or conventional) meaning, go beyond it, and are strongly polysemic units in the Quechua language and culture. In this research, we analyze the somatic lexemes uma 'head' and simi 'mouth', which show a complex conceptual universe, and form a semantic network provided with an internal radial structure. In particular, our goals are twofold. On the one hand, we want to identify all those concepts that these two linguistic forms related to human biology Quechua, is associated. Moreover, we intend to explain how these new concepts have come to be associated with somatic lexemes mentioned before. To do this, we will build on the theoretical and methodological principles of the discipline called cognitive linguistics (Lakoff and Johnson 1980, Langacker 1987, Lakoff 1987, among others), and propose the metaphor and metonymy as those mechanisms responsible for the extension of meanings.